Evaluasi PCK (Pedagogical Content Knowledge) Dalam Kesiapan Mahasiswa Pendidikan Biologi Sebagai Calon Tenaga Pendidik - Nurhidayah; Mohammad Mulyadi Prasetyo; Khaidarsyah (Biosfer : Jurnal Biologi dan Pendidikan Biologi, 2023)
Knowledge of Pedagogical Content (PCK) is a concept that emerged because the teaching process not only provides knowledge to students but also gives them the ability to apply the knowledge they acquire. PCK needs to be owned by teaching staff or prospective teaching staff to determine the strategies or techniques used to convey lesson material so that it is more efficient and meaningful. Apart from that, PCK is also one of the standards for preparing teaching staff. The aim of this research is to evaluate the PCK (pedagogical content knowledge) of biology education students regarding their readiness to become teaching staff. This research applies a descriptive approach and is quantitative. A total of nine biology education students were used as research subjects. Samples were taken using purposive sampling. PCK data was obtained through a questionnaire, while data on teaching ability was taken through an assessment sheet. Data were classified based on score interpretation criteria and analysed descriptively with percentages. The results of this research show that PCK is included in the good category with a percentage of 77.72%, and basic teaching abilities are also included in the good category with a percentage of 78.92%. Teachers with good PCK can organise learning well. Because students gain a lot of experience during the learning process, teaching ability is also important for the success of the learning process. The results of this research show that biology education students have good PCK, indicating that they are ready to become educators